2021
DOI: 10.2147/ijgm.s325112
|View full text |Cite
|
Sign up to set email alerts
|

Independent Risk Factors for the Dynamic Development of COVID-19: A Retrospective Study

Abstract: Objective To identify the risk factors for predicting the dynamic progression of COVID-19. Methods A total of 2321 eligible patients were included in this study from February 4 to April 15, 2020. Two illness conditions, including mild/moderate (M/M) subtype to severe/critical (S/C) and S/C to fatality, were classified. Clinical message was collected and compared, respectively. Kaplan–Meier method, Cox regression model and risk score system were used to predict disease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Several studies have demonstrated the association between certain clinical characteristics, such as an older age, male sex, symptoms of COVID-19 (a fever, cough, fatigue, and shortness of breath), and comorbidities (hypertension, diabetes, and CKD) and the disease severity or activity [ 21 23 ]. The addition of blood tests may also increase the accuracy of prediction of disease progression [ 11 ]. However, involving blood sampling would make it difficult for medical staff to immediately evaluate patients’ risk while in their presence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the association between certain clinical characteristics, such as an older age, male sex, symptoms of COVID-19 (a fever, cough, fatigue, and shortness of breath), and comorbidities (hypertension, diabetes, and CKD) and the disease severity or activity [ 21 23 ]. The addition of blood tests may also increase the accuracy of prediction of disease progression [ 11 ]. However, involving blood sampling would make it difficult for medical staff to immediately evaluate patients’ risk while in their presence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some biomarkers have been reported to be associated with disease severity [ 4 , 8 12 ]. Using these risk factors, several investigators have reported risk stratification methods [ 9 11 , 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leukocytosis has been associated with disease progression and severity 27 , 28 , 29 , and studies have found that lymphopenia is associated with disease severity and with worse outcomes. 29 , 30 , 31 , 32 , 33 Thrombocytopenia has been routinely observed in patients with COVID-19, with lower platelets manifesting in severe and critical illness 34 and being associated with higher mortality. 35 Additionally, worse outcomes have been observed in patients with elevations in numerous, routinely available inflammatory markers: D-dimer, C-reactive protein, lactate dehydrogenase, and ferritin.…”
Section: Introductionmentioning
confidence: 99%